2013
DOI: 10.12811/kshsm.2013.7.1.069
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Internal Marketing Activities, Job Satisfaction, Organizational Commitment, and Turnover Intention in Pharmaceutical Companies -Focusing on Pharmaceutical Salespeople-

Abstract: The initial approach to this study is to focus on pharmaceutical companies' internal marketing activities for organizational diagnosis.By analysing the influence of internal marketing elements on the job satisfaction, organizational commitment, and turnover intention of pharmaceutical salespeople, this study aims at coming up with ways to strengthen the sales capacity and competitive edge of pharmaceutical companies through the salespeople's satisfaction. For 32 days between November 10th and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The communication, training, and continuous support included in IB within the organization could have a significant impact on lowering TI [66]. However, these activities do not necessarily result in a decrease in the TI of employees [67], and there are differences in the impact on TI depending on the factors which make up the IB activities [39,68]. In this regard, various previous studies that set organizational effectiveness and performance as dependent variables focused on the mediating role of WE.…”
Section: Mediating Effect Of Wementioning
confidence: 99%
“…The communication, training, and continuous support included in IB within the organization could have a significant impact on lowering TI [66]. However, these activities do not necessarily result in a decrease in the TI of employees [67], and there are differences in the impact on TI depending on the factors which make up the IB activities [39,68]. In this regard, various previous studies that set organizational effectiveness and performance as dependent variables focused on the mediating role of WE.…”
Section: Mediating Effect Of Wementioning
confidence: 99%
“…The higher the score, the greater the turnover intention. To set the independent variables to be included in the turnover-related factors, we referenced previous studies based on the three categories, items whose statistical signi cances had been demonstrated in previous studies (Cotton and Tuttle's study (17), Lee and Mowday's study (18), Song's study (19), Smith, Kandell, and Hulin's study (20), and Cha, Ryu, and Lee's study (21) were selected as variables (55 items).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…As for the "organization-related factor category," corporate culture, supervisor (17), colleague (17), organization commitment (20,21), and social evaluation and perception of the company were included as independent variables (21 items). Organizational commitment (four items) (20,21) was shown to have a signi cant impact on turnover intention (21) and was included along with the supervisor ( ve items) and colleague (four items) variables (17).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
See 1 more Smart Citation